Base temperature and plastochron are influenced by the development phase in biquinho pepper cultivars - Valera, Oscar Valeriano Sánchez; Diel, Maria Inês; Pinheiro, Marcos Vinícius Marques; Thiesen, Leonardo Antonio; Caron, Braulio Otomar; de Paula, Gizelli Moiano; Holz, Ezequiel; Altissimo, Bruna Stringari; Schmidt, Denise (Comunicata Scientiae, 2022)
The objective was to estimate the base temperature and determine the plastochron for Capsicum chinense cultivars during the vegetative and reproductive development phases at different planting times. The experiment was conducted in a randomized block design, 2x4 factorial scheme, cultivars of biquinho pepper (“BRS Moema”, “Airatema Biquinho Amarela”) and growing seasons (E1-E2-E3-E4). The Air temperature was monitored during the vegetative and reproductive phases of the crop. Tb was determined by the minimum mean square error method (QMe). For both phases of the crop development, plastochron was determined by linear regression between the number of nodes and the accumulated thermal sum (Sta). Tb and plastochron were not influenced by the cultivar. In the vegetative phase, Tb and plastochron were dependent on the sowing season, presenting on average Tb (16.8°C) and plastochron (43.6°C day-1). In the reproductive phase both Tb and plastochron were similar at all sowing times, with averages of 16.7°C and 64.4°C day-1 plastochron, for base temperature and plastochron, respectively. Therefore, the emission of nodes is not influenced by the cultivar, but by growing season. With the plastochron values found it is concluded that the development of biquinho pepper is more accelerated during the vegetative phase than the reproductive one.